THU0424 Treatment with Tnf Alpha Blockers Is Associated with Reduced Progression of Atherosclerotic Plaques in Patients with Psoriatic Disease – A Prospective Study. (15th July 2016) - Eder, L.; Chandran, V.; Cook, R.; Gladman, D.D.
Abstract : Background: Patients with psoriatic disease are at high risk for cardiovascular morbidity. The strong link between inflammation and atherosclerosis highlights the role of suppression of inflammation as a potential strategy for prevention of cardiovascular events. Objectives: To assess whether the use of TNFα blockers is associated with reduced rate of progression of atherosclerotic plaques in psoriatic disease patients. Methods: Patients with psoriasis only (PsC) or psoriatic arthritis (PsA) from a large psoriatic disease cohort were enrolled. Baseline evaluation included clinical assessment of cardiovascular risk factors, joint and skin disease activity and medication use. Patients were followed every 6–12 months according to a standard protocol. Treatment with any TNFα blocker for at least 50% of the follow-up period was defined as the primary predictor. Ultrasound assessment of the carotid arteries was performed and Total Plaque Area (TPA) was measured at baseline and after 2–3 years. The average annual change in TPA was calculated by subtracting the baseline from the follow-up TPA divided by the number of years between the visits. This measure represented the annual progression rate of atherosclerosis and was considered the outcome of interest. The association between treatment with a TNFα blocker and progression of atherosclerosis was assessed by multivariate linear regression analysis after adjusting for cardiovascular risk factors, statin therapy and treatment with Disease Modifying Anti Rheumatic Drugs (DMARDs). Results: A total of 319 patients with psoriatic disease (66.4% PsA, 33.6% PsC) were included in the analysis. Their mean age was 54.5±11.8 years and 56.3% were men. The mean duration of follow up was 2.9 years. 61.7% of the patients had at least one atherosclerotic plaque at baseline. Progression in atherosclerosis was observed in 46% of the patients, while in the remaining 54% no change/regression in atherosclerosis was found. Men had a significantly higher annual progression rate of atherosclerosis compared with women (annual TPA 2.4 vs. 0.6 mm 2, p<0.001, respectively). Since a statistically significant interaction between sex and several of the co-variates, including TNFα blocker therapy, was found, separate regression models were constructed for men and women. In men, TNFα blocker therapy was associated with a reduced adjusted rate of atherosclerosis progression (β=-2.25 95% Confidence Interval (CI) -3.45, -1.05, p<0.001). Additional predictors of atherosclerosis progression in men were baseline TPA (β =5.72, 95% CI 3.81, 7.62), current smoking (β=1.86, 95% CI 0.19, 3.54) and LDL cholesterol level (β=0.81, 95% CI 0.07, 1.56). In contrast, neither TNFα blocker therapy (p=0.71) nor any of the cardiovascular risk factors assessed predicted progression rate of atherosclerosis in women. No difference was found in atherosclerosis progression between PsA and PsC (p=0.73). Conclusions: TNFα blocker therapy is associated with reduced progression rate of atherosclerosis in patients with psoriatic disease. The lack of association in women may be explained by reduced power due to minimal progression of atherosclerotic plaques in women in general or by alternative underlying mechanisms of cardiovascular morbidity in women. Disclosure of Interest: L. Eder Grant/research support from: Abbvie, V. Chandran Grant/research support from: Abbvie, Consultant for: Abbvie, Amgen, Celgene, Janssen, Novartis, UCB, R. Cook: None declared, D. Gladman Grant/research support from: Abbvie, Eli Lilly, Pfizer, Amgen, Celgene, Janssen, Novartis, UCB, Consultant for: Abbvie, Eli Lilly, Pfizer, Amgen, Celgene, Janssen, Novartis, UCB